Absence of 2009 pandemic H1N1 influenza A virus in fresh pork. - Amy L Vincent (PLoS ONE, 2009)
The emergence of the pandemic 2009 H1N1 influenza A virus in humans and subsequent discovery that it was of swine influenza virus lineages raised concern over the safety of pork. Pigs experimentally infected with pandemic 2009 H1N1 influenza A virus developed respiratory disease; however, there was no evidence for systemic disease to suggest that pork from pigs infected with H1N1 influenza would contain infectious virus. These findings support the WHO recommendation that pork harvested from pandemic influenza A H1N1 infected swine is safe to consume when following standard meat hygiene practices.